Relationship between Smartphone Use with Sleep Quality of SMAN 1 Mataram in Mataram City and SMAN 1 Gunungsari in West Lombok Regency - Raehanah, Yunda Riana Dini Hariani; Mahardika, Agustine; Niti Wedayani, AA Ayu (Faculty of Medicine Universitas Mataram, 2019)
Background : Smartphone usage has increased over the past decade, especially among adolescents. Excessive use can present unhealthy and uncontrolled habits called addictions. Exposure to blue light on a smartphone can disrupt circadian rhythms and affect sleep quality. The purpose of this study was to determine the relationship between smartphone use and sleep quality amount students of SMAN 1 Mataram in Mataram City and SMAN 1 Gunungsari in West Lombok Regency. Method : This study is a descriptive analytic study using a cross sectional approach to 150 students taken by purposive sampling. Data on smartphone addiction was collected by filling in the Smartphone Addiction Scale-Short Version questionnaire and sleep quality data collected by filling in the Pittsburgh Sleep Quality Index questionnaire. The data analysis using Gamma statistical tests. Result : In this study, there was 77 students (51,3%) had a smartphone addiction and 55 students (26,7%) with a high risk of smartphone addiction, whereas in terms of sleep quality 90 students (60% %) experienced poor sleep quality. Based on Gamma statistical test analysis, the significance value of p = 0.017 and the correlation coefficient r = -0.339 were obtained. Conclusion : There is a significant relationship between smartphone use and students sleep quality. It is expected that students may be able to control their use of smartphone to gain better sleep quality.